Storytelling for storytelling â€œKlinik Kopiâ€ Yogyakarta - Virginia Ayu Sagita; Medi Trilaksono Dwi Abadi; Mochammad Fauzul Haq; Revta Fariszy; Keny Rahmawati (The Indonesian Journal of Communication Studies, 2023)
The development of the current coffee shop is very rapid. This condition is proven by the growth of new coffee shops scattered throughout the city. In the Special Region of Yogyakarta, there are approximately 3,000 coffee shops. The research focuses on one of the coffee shops that are quite famous and interesting in Yogyakarta because it is included in one of the Ada Apa Dengan Cinta (AADC) 2 movie scenes, namely Klinik Kopi. Qualitative methods and data collection techniques with in-depth interviews and observations were used in this study. The conclusion from this study is that storytelling is used in Coffee Clinic marketing, which is a form of soft selling using the message design logic from Barbara O'Keefe to attract consumers amid the many coffee shop competitions in Yogyakarta, and the 4P marketing mix does not run significantly in Coffee Clinic marketing. The owner has his way of designing the message he wants to convey to his consumers. The communicant has the same opinion about a coffee story, which is interesting to hear from the communicator.